How is forest restoration plantations\' functioning affected by tree diversity? - Duarte, Marina Melo (2018)
Tropical forests restoration is an important tool for climate change mitigation and biodiversity conservation. We can ally both of these elements, according to the biodiversity and ecosystem (BEF) functioning theory, which says that diversity enhances ecosystem functions, as primary productivity. Nevertheless, the greatest part of BEF studies up to very recently have focused on grasslands and not on as complex ecosystems as tropical forests. It is necessary to better understand above- and below-ground processes through which biodiversity acts on ecosystem functions. This work aimed to investigate effects of tree richness on both above- and below-ground ecological processes. It was based on two tropical forests undergoing restoration, in Sardinilla (Panama) and in Anhembi (Brazil). The former was especially designed for BEF studies and allowed to untangle effects of biodversity on ecosystem functions. The latter had more than a hundred species in plots and permitted investigation of the effects of high tree richness levels. In both Sardinilla and Anhembi, we investigated if tree richness levels affected an above-ground ecological process, light interception, and which mechanisms could be related to it. Richness could enhance light interception and mechanisms as spatial (horizontal and vertical) and temporal light distribution. It promoted both selection and complementarity effects. In Anhembi, we investigated if species richness influenced below-ground processes related to soil carbon stocks. Stand richness enhanced fine root production and stock. Effects of stand number of species on litter decomposition and stock were not linear. Richness of litter content, however, did not affect its decomposition rates. Number of stand species did not influence litter production. Differences of litter production, stock and fine root production among distinct richness levels did not change over the time. However, distribution of fine roots over the space, within different layers of soil, was affected by number of tree species. We concluded that even very high richness levels could not saturate some of the ecological processes studied. Diversity acted on both above- and below-ground processes, in various and sometimes opposite ways, counting on multi-direction feedbacks. It is very important to understand these mechanisms in order to potencialize biodiversity convervation and carbon sequestration by tropical forest restoration. Future studies may focus on untangling effects of diversity on below-ground processes (which have not been exhaustively explored in research), on understanding how high diversity levels affects natural regeneration and on investigationg functional traits provided by different species.